Newest Drugs Of Lung Cancer That’s Approved In 2020 (Article Review) - Mohammed, Zainab Sajid; Hamza Al-Kraity, Asst.Prof.Dr. Wijdan Rajh; AL-Fatlawy, Hawraa Natiq Kabroot (Medical Science Journal for Advance Research, 2023)
Background: Male patient incidence rates have been declining in most affluent countries since the mid-1990s, while female patient incidence rates have been steadily rising. As a result, lung cancer incidence rates in male and female patients have converged in the United States and other industrialized countries, particularly among the younger population. Variances in sex-based lung cancer incidence may be due to sex-specific differences in histological subtypes of lung cancer, as well as changes in smoking prevalence. Tobacco use, a family history of cancer, past lung disorders, and exposure to secondhand smoke, radon, asbestos, arsenic, air pollution, or occupational carcinogens are all common risk factors for lung cancer. Lung cancer subgroups have diverse epidemiological and prognostic characteristics. Small cell lung cancer (SCLC) and squamous cell carcinoma have both been linked to smoking as a major risk factor. In the Western population, smoking is responsible for more than 80% of lung cancer etiology. Lung cancer has been reduced as a result of tobacco control measures such as higher cigarette taxes and pricing, health warnings on packaging, and smoking cessation counseling, as well as a comprehensive ban on tobacco advertising. Adenocarcinoma, on the other hand, is more common in Asians, particularly among females and never-smokers. There is extensive data on the prevalence of EGFR mutations in adenocarcinoma patients, with the highest EGFR mutation frequency of 47 percent in Asia-Pacific and the lowest frequency of 12 percent in Oceania. The development of lung adenocarcinoma in Asian nonsmokers has been linked to strong exposure-response correlations with secondhand smoke and cooking gases, according to studies conducted in China and Hong Kong. Cancer registries that track the efficacy of cancer prevention and treatment techniques are critical for assessing the present cancer burden on healthcare systems and monitoring the efficacy of cancer prevention and treatment strategies. In terms of lung cancer epidemiology in Taiwan, worldwide cancer surveillance data was inadequate, and material from prior studies had grown outdated. We were able to update the changes in the prevalence, incidence, and overall survival of individuals with cancer in this population-based epidemiologic investigation.